Heavy metals in wastewater and fish collected from waste stabilization pond and human health risks in southwestern Ethiopia - Berhanu, Girma; Lemma, Hailu; Mekonnen, Seblework; Dadi, Dessalegn (Frontiers in Environmental Health, 2024)
Introduction: This study was conducted to measure the concentration of toxic heavy metals in wastewater samples, Nile Tilapia (Oreochromis niloticus) species breeding in wastewater (waste stabilization ponds), and their safety as source of food in southwestern Ethiopia. For this purpose, toxic metals like lead (Pb), cadmium (Cd), arsenic (As), and mercury (Hg) in wastewater samples and fish tissues (muscle, gill, and liver) were independently examined.Methods: A laboratory-based cross-sectional study was performed to ascertain the levels of lead (Pb), cadmium (Cd), arsenic (As), and mercury (Hg) in the fish tissues of Oreochromis niloticus and wastewater samples. Heavy metals levels were analyzed by Microplasma Atomic Emission Spectrometry (Agilent 4210 MP-AES) and Hydrogen-Generated Atomic Absorption Spectrometry (HGAAS, novAA 400P, Germany). Results: Heavy metal concentrations were measured in the following decreasing order (µg l -1 ): Cd > Pb > As > Hg in facultative and maturation ponds, with Cd (27.66 µg l -1 ) having the highest concentration and Hg (0.349 µg l -1 ) the lowest. Among the heavy metals detected in wastewater samples, Hg showed a statistically significant difference between sampling points (p = 0.023). The maximum metal concentration was measured for Pb (0.35 mg kg -1 ) and Cd (0.24 mg kg -1 ) in the muscle tissue of O. niloticus. The value of arsenic (0.02 mg kg -1 ) detected in the fish's edible muscles exceeded the FAO/WHO maximum permissible limit (MPL = 0.01) for human consumption. The carcinogenic and non-carcinogenic health risks of consuming fish due to trace metals were relatively low and pose fewer potential threats to human health. According to this finding, children were more susceptible to heavy metal exposure than adults. Conclusion: Because of the high quantities of these harmful heavy metals, wastewater from oxidation ponds should not be used for fishing to avoid bioaccumulation. The target carcinogenic risk (TR) and target hazard quotient THQ indicated that all heavy metals were below the safe threshold. This research will provide a baseline for monitoring trace metals in various edible aquatic creatures, as well as for future research in artificial habitats and regulatory considerations.